2020
DOI: 10.3847/1538-3881/ab6ced
|View full text |Cite
|
Sign up to set email alerts
|

Size and Shape Constraints of (486958) Arrokoth from Stellar Occultations

Abstract: We present the results from four stellar occultations by (486958) Arrokoth, the flyby target of the New Horizons extended mission. Three of the four efforts led to positive detections of the body, and all constrained the presence of rings and other debris, finding none. Twenty-five mobile stations were deployed for 2017 June 3 and augmented by fixed telescopes. There were no positive detections from this effort. The event on 2017 July 10 was observed by SOFIA with one very short chord. Twenty-four deployed sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…No periodic brightness variation due to rotation was detected in Hubble Space Telescope (HST) photometry before the flyby, with an upper limit amplitude of about 0.15 magnitudes (10). Stellar occultations in July 2017 and August 2018 showed that Arrokoth had an elongated, possibly contact-binary shape (11). The elongated shape and the low lightcurve amplitude implied that Arrokoth's rotational pole was roughly aligned with the direction of the Sun and Earth.…”
Section: Rotation and Global Shape Modelingmentioning
confidence: 99%
“…No periodic brightness variation due to rotation was detected in Hubble Space Telescope (HST) photometry before the flyby, with an upper limit amplitude of about 0.15 magnitudes (10). Stellar occultations in July 2017 and August 2018 showed that Arrokoth had an elongated, possibly contact-binary shape (11). The elongated shape and the low lightcurve amplitude implied that Arrokoth's rotational pole was roughly aligned with the direction of the Sun and Earth.…”
Section: Rotation and Global Shape Modelingmentioning
confidence: 99%
“…It is a bilobate body with a larger lobe measuring approximately 20 × 20 × 10 km and a smaller lobe of 15 × 14 × 10 km, connected by a very thin neck (Spencer et al 2020). Arrokothʼs contact-binary nature was first determined by a stellar occultation and then confirmed with resolved New Horizons images (Stern et al 2019;Buie et al 2020). Because the Kuiper Belt is a population of objects that have been mostly isolated since they first formed from the protoplanetary disk (Levison et al 2008;Nesvorný et al 2010), small TNO shapes must illustrate fundamental accretionary processes.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Gaia EDR3 (Lindegren et al 2020) provides star positional knowledge to a precision of a few milliarcseconds per occultation star, equating to a few kilometers of uncertainty in the ground track of an occultation. Arrokoth is the only small TNO that has been observed with a high-cadence occultation campaign, which revealed its contact-binary shape (Buie et al 2020). But this powerful technique can and should be extended to determine the nature and origin of other small TNOs.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of the Canadian extension to the RECON network, the (C-06) Anarchist Mountain Observatory team recorded data for the January event with a QHY174M-GPS. This is the same camera used to obtain the occultation measurement on Arrokoth (Buie et al 2020b). As opposed to the video data recorded by the standard RECON setup, the QHY system writes each single integration directly to a FITS frame, with GPS location and timing data written into the image header.…”
Section: Qhy Cmos Datamentioning
confidence: 99%